Convergence of Blockchain, Autonomous Agents, and Knowledge Graph to Share Electronic Health Records - Yao, Yao; Kshirsagar, Meghana; Vaidya, Gauri; Ducrée, Jens; Ryan, Conor (Frontiers in Blockchain, 2021)
In this article, we discuss a data sharing and knowledge integration framework through autonomous agents with blockchain for implementing Electronic Health Records (EHR). This will enable us to overcome the issues inherent in traditional EHRs. We discuss how major concerns in the health industry- viz, trust, security can be addressed by transitioning from existing models to convergence of the three technologies in a decentralised ecosystem. Each autonomous agent is responsible for instantiating a key process (user authentication and authorization, smart contract, knowledge graph) among the participating stakeholders in the network thereby eliminating the dependency on third party vendors. We claim that these features of the system guarantee a better, safer clinical decision making and pave the way towards more informed and engaged patients and citizens by delivering personalized healthcare.